SAHAM DAN PASAR MODAL SYARIAH: KONSEP, SEJARAH DAN PERKEMBANGANNYA - Muhammad Yafiz (MIQOT: Jurnal Ilmu-ilmu Keislaman, 2008)
Abstract: Share and Syari’ah Stock Market: Concept, History and Development. This paper is an attempt to analytically describe limited sharesand capital market in syari’ah perspective. In so doing, this paper tries to elaborate their implementation in financial sectors in Islamic countries. It traces the historical development of the shares and capital market. It also compares the implementation in other countries such as United States, Malaysia and Indonesia.Kata Kunci: pasar modal, saham, keuangan syariah